2009
DOI: 10.1584/jpestics.g08-32
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity difference to insecticides of a riverine caddisfly, Cheumatopsyche brevilineata (Trichoptera: Hydropsychidae), depending on the larval stages and strains

Abstract: To determine sensitivity to fenitrothion (MEP), fenobucarb (BPMC) and imidacloprid (IMI) in each larval instar of Cheumatopsyche brevilineata, we carried out 48-hr acute toxicity tests using strains M and K originating from an urban river and an irrigation canal, respectively. First instar was the most sensitive stage to all three insecticides whereas fifth instar was the most insensitive in both strains. Larvae of strain K were significantly more insensitive to MEP through larval growth and to BPMC in second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The embryo of the grass shrimp, Palaemonetes pugio, is less sensitive to etofenprox than are the adult and larval life stages (DeLorenzo and De Leon 2010). In contrast, the LC50 overall values from my experiment II were similar to the 48h median effect concentration (EC50) value of 0.116 μg/L for first-instar larvae of C. brevilineata (Yokoyama et al 2009b), which were the most sensitive of the larval instars to several insecticides (Yokoyama et al 2009c). Moreover, my LC50 overall values were comparable to the HC5 value of 0.085 μg/L estimated from a species sensitivity distribution analysis of etofenprox using reliable acute toxicity data in aquatic invertebrates (Nagai 2016), and they were also close to fieldrelevant concentrations: etofenprox has been detected at maximum concentrations from 0.04 to 0.16 μg/L in water samples from rivers and a canal flowing through paddy field areas in Japan (Tanabe and Kawata 2009;Añasco et al 2010).…”
Section: Diflubenzuron Experimentsmentioning
confidence: 58%
See 1 more Smart Citation
“…The embryo of the grass shrimp, Palaemonetes pugio, is less sensitive to etofenprox than are the adult and larval life stages (DeLorenzo and De Leon 2010). In contrast, the LC50 overall values from my experiment II were similar to the 48h median effect concentration (EC50) value of 0.116 μg/L for first-instar larvae of C. brevilineata (Yokoyama et al 2009b), which were the most sensitive of the larval instars to several insecticides (Yokoyama et al 2009c). Moreover, my LC50 overall values were comparable to the HC5 value of 0.085 μg/L estimated from a species sensitivity distribution analysis of etofenprox using reliable acute toxicity data in aquatic invertebrates (Nagai 2016), and they were also close to fieldrelevant concentrations: etofenprox has been detected at maximum concentrations from 0.04 to 0.16 μg/L in water samples from rivers and a canal flowing through paddy field areas in Japan (Tanabe and Kawata 2009;Añasco et al 2010).…”
Section: Diflubenzuron Experimentsmentioning
confidence: 58%
“…They are suited for use in environmental impact assessments because of their high species diversity and their importance in the functioning of aquatic ecosystems (Rosenberg et al ). The impacts of pesticides on larvae of aquatic insects have attracted interest from many ecotoxicological researchers (Peterson et al , ; Beketov and Liess , ; Yokoyama et al , ). Several researchers have performed experiments using the eggs of aquatic insects to clarify the effects of insecticides on embryonic stages.…”
Section: Introductionmentioning
confidence: 99%
“…Yokoyama et al (2009c) also examined toxicity of fenitrothion, along with fenobucarb and imidacloprid, on larval stages of the caddisfly Cheumatopsyche brevilineata.Based on 48-hour acute toxicity tests using two larval strains, the authors found that first instar larvae were the most sensitive to all pesticides, and the fifth instar stage was least sensitive. Sensitivity also varied between the strains tested for fenitrothion and fenobucarb Gaworecki et al (2009).…”
mentioning
confidence: 99%